The role of gut microbiota in the development of autoimmune disease - a literature review - Baran, Karolina; Marlena Jankowska,; Natalia Jańczyk,; Karolina Mędrysa,; Jakub Pokrzepa,; Michał Presak,; Gabriela Blecharz,; Julia Szwech,; Mikołaj Pograniczny,; Adrianna Mielżyńska, (Quality in Sport, 2025)
The gut microbiota plays a crucial role in maintaining immune balance, and its dysregulation has been increasingly linked to the development of autoimmune diseases. This review summarizes evidence connecting microbial alterations to conditions such as type 1 diabetes, rheumatoid arthritis, multiple sclerosis, and inflammatory bowel disease. Changes in microbial diversity and the overgrowth of pro-inflammatory species appear to trigger immune pathways that drive disease progression. Therapeutic strategies aimed at restoring gut balance, including probiotics, prebiotics, fecal microbiota transplantation (FMT), and dietary and lifestyle interventions, show promise in modulating immune responses and improving outcomes. However, despite encouraging results, significant gaps remain regarding the causality of these associations, the long-term safety of interventions like FMT, and the need for individualized therapeutic approaches. Advances in microbiome research, including metagenomic profiling, offer hope for developing personalized treatments. Further studies are necessary to better understand the complex interactions between the gut microbiota and the immune system in autoimmune diseases.